Ibn Zumarak's Poetry: A Study of the Contrast of Themes (Journal of Misan Researches, 2025)
In this research, we seek to study the contrast of topics in the poetic verses of Ibn Zamrak, with an explanation of how these poetic verses differ in describing a specific topic of the poetic topics. The aim of studying the thematic contrast between the poetic verses was to reach a certain result in favoring one of the poetic verses that we contrasted between in a certain situation or equating them. We found this meaning in poetic verses by Ibn Zamrak, some of which are related to praise and elegy, and some in his poems known as morning poems, and even what was written as inscriptions on the walls and doors of the palace. The method followed in the research was the analytical description method.